Transformasi Bisnis Digital Untuk Meningkatkan Daya Saing UMKM Batik Tulis Pancor Emas Desa Bucor Kulon Kecamatan Pakuniran Probolinggo - Junaedi, Deddy; Diana, Avinda; Fiardilah, Kholifatul; Sa’adah, Rashika Nabilatus; Hukmah, Safiroh (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Digital transformation in MSMEs refers to the use of information and communication technology to increase efficiency, productivity and business competitiveness. Pancor Mas Written Batik from Bucor Kulon Village, Pakuniran District, Probolinggo Regency is one of Indonesian cultural products that has great potential to be developed. Digital business transformation is an important strategy in increasing the competitiveness of the MSME market. By adopting digital technology, it is hoped that Written Batik MSMEs can expand their market reach, increase operational efficiency, and provide added value to their products. The aim of this research is to identify challenges in the adoption of digital technology by the Batik Tulis Pancor Emas MSMEs in Bucor Kulon Village. This research uses a qualitative approach by taking primary data sources in the form of interviews, secondary data in the form of literature studies. The qualitative research paradigm is research that places humans as research subjects. The findings in this research show that the majority of Pancor Emas Batik Tulis MSME owners show a good understanding of the importance of digitalization, they realize that digital technology helps in marketing, inventory management, and communication with customers. The business has been running for more than 10 years, the number of employees is 7 people, the business owner's latest education is high school. From the level of adoption of digital technology, Batik Tulis Pancor Emas MSMEs still do not use e-commerce but use conventional marketing using outlets or kiosks spread across several places. MSMEs do not use E-Commerce in their sales so they do not experience significant sales, while MSMEs that have used E-Commerce have experienced an increase in sales.